2003
DOI: 10.1046/j.1460-9568.2003.02446.x
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin transporter intronic VNTR enhancer correlated with a predisposition to affective disorders has distinct regulatory elements within the domain based on the primary DNA sequence of the repeat unit

Abstract: We have demonstrated that a variable number tandem repeat domain (VNTR) within intron 2 of the serotonin transporter gene is a transcriptional regulatory domain which is potentially correlated with a predisposition to affective disorders and other behavioural conditions. This correlation based on copy number of the VNTR alone (nine, 10 or 12 copies of 16/17 base-pair element) has been controversial and not reproduced in all studies. We demonstrate that individual repeat elements within the VNTR domain differ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 18 publications
4
70
1
Order By: Relevance
“…Particular emphasis has been placed on functional variants in the serotonin transporter gene (SERT, 5-HTT, SLC6A4), given an etiopathological hypothesis based on the effectiveness of serotonin reuptake inhibitors in the treatment of OCD. Studies have investigated common non-coding variants affecting transcriptional efficiency, such as the 43 bp promoter indel referred to as 5-HTTLPR and STin2, a variable number of tandem repeats polymorphism in intron 2 (Heils et al, 1995;Hranilovic et al, 2004;Hu et al, 2006;Lesch et al, 1995;Lovejoy et al, 2003;MacKenzie and Quinn, 1999). Rare coding mutations such as the gain-of-function I425V have also been reported as segregating in families with OCD probands (Ozaki et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Particular emphasis has been placed on functional variants in the serotonin transporter gene (SERT, 5-HTT, SLC6A4), given an etiopathological hypothesis based on the effectiveness of serotonin reuptake inhibitors in the treatment of OCD. Studies have investigated common non-coding variants affecting transcriptional efficiency, such as the 43 bp promoter indel referred to as 5-HTTLPR and STin2, a variable number of tandem repeats polymorphism in intron 2 (Heils et al, 1995;Hranilovic et al, 2004;Hu et al, 2006;Lesch et al, 1995;Lovejoy et al, 2003;MacKenzie and Quinn, 1999). Rare coding mutations such as the gain-of-function I425V have also been reported as segregating in families with OCD probands (Ozaki et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…1). We have demonstrated that the different repeat number within the VNTR supports differential expression in vitro (Fiskerstrand et al, 1999;Lovejoy et al, 2003) and both differential and tissuespecific expression in vivo (MacKenzie and Quinn, 1999) in a transgenic model. It has also been demonstrated that the VNTR genotype correlates with the number of platelet 5-HTT transporters in patients with affective disorders (Mellerup et al, 2001).…”
Section: Introductionmentioning
confidence: 78%
“…We have previously demonstrated the ability of the VNTR domains to support reporter gene expression in vivo and in vitro (Fiskerstrand et al, 1999;MacKenzie and Quinn, 1999;Lovejoy et al, 2003). To further investigate the ability of YB-1 to regulate the VNTR domains, we used luciferase reporter gene constructs containing VNTR domains inserted upstream of the SV40 promoter termed pStin2.9Luc, pStin2.10Luc, and pStin2.12 Luc.…”
Section: Yb-1 Can Specifically and Differentially Activate The Distinmentioning
confidence: 99%
“…Functionally, the alleles of STin2 VNTR (STin2.10 and STin2.12) can act as transcriptional regulatory elements, with STin2.12 having a superior enhancer-like property within the developing rostral hindbrain, which may lead to aberrant serotonergic neuron development. 32,33 In spite of the evidence for functional effects of alleles at STin2 VNTR, it is not possible to determine whether this VNTR is causally associated with increased risk of schizophrenia. It has been suggested that individual polymorphisms have a weak influence when compared with the combined effect of 5-HTTLPR and STin2 VNTR polymorphisms on SLC6A4 expression.…”
Section: Discussionmentioning
confidence: 99%